Restrictive use of interpretation of language actions in legal construction - Romadhon, Ahmad Heru; Lapasere, Fachria; Wardantik, Yuli Endah (Electronic Journal of Education, Social Economics and Technology, 2022)
The purpose of this study is to understand the essence of language action in legal construction as a means of communication that should rely on language grammar in interpreting the meaning of sentences. Such a method is an attempt to avoid the different interpretations of the multiple interpretations of the meaning of language. The simplification of legal language must be linked to the content of the rules, where there are two arguments regarding "intentions and extensions", before carrying out legal interpretation, then interpretation is generally understood as a process, action, series of interpreting and explaining the meaning of something that is less clear or opinion, view of the context in which it is interpreted. This study uses a normative juridical method that explains the interpretation of manuscripts, legal principles and principles, legal rules, theories and legal doctrines that apply as a tool to understand the meaning of legal language communication and to understand the substance of a statutory regulation. The research approach uses a conceptual approach to examine and examine the subject matter. The consequences of blurred inter-connections result in a disparity in the factual application of the law which is correlated with a “policy during decision-making” in a formulaic policy which is a “policy” context. Based on these aspects, especially in language action, it is essentially an "effort in realizing clarity of meaning in laws and regulations so that they are in accordance with current and future implementation and conditions.